Angeles Community Health Complex a primary care and outpatient center integrated with civic-recreation spaces - Capuli, Stella Marie V.
Health is a fundamental right, regardless of race, religion, economic or social status (Ghebreyesus, 2017). Given the fragmented health situation of the Philippines (WHO, 2012), the country is far from achieving accessible health for all, especially with design of the healthcare environment. The built environment is a major aspect affecting health and wellbeing. Ulrich and Zimring, found that there are more than 600 studies linking the design of the built environment and its effects on staff stress and effectiveness, patient safety, stress and healing, and overall quality of health. (Ulrich & Zimring, 2004). The current trend in the health care environment is largely process-oriented, which results in an intimidating and complicated experience of seeking health services. With the recently signed Universal Health Care Law relaxing the financial barrier to accessible healthcare, this study explores how the architecture and design of a healthcare environment under the new law can extend benefits to both patients and non-patients.